Explanation On The Application Of Legal Language In The Context Of Criminal Actions - Saiful Hi. Soleman Nur (International Journal Of Community Service, 2022)
Counseling in the legal language organized by the North Maluku Province language office. What the resource persons present is related to language in law. Therefore, the discussion is in Counseling on the Application of Legal Language in the Context of Criminal Acts. This outreach activity is very beneficial for all parties, both the community and practitioners, especially in the field of law, the language used in cyberspace must speak words in conveying or short messages must be good and polite so as not to isolate a party to the point of criminal acts or offences for peopleother.